이종복합보드의 동적탄성률에 미치는 녹차와 톱밥 배합비율의 영향 및 정적 휨 강도성능의 예측 - 박한민; 이수경; 석지훈; 최남경; 권창배; 허황선; 변희섭; 양재경; 김종철; Han-Min Park; Soo-Kyeong Lee; Ji-Hoon Seok; et al. (농업생명과학연구, 2012)
이 연구에서는 선행연구의 녹차-목재섬유 복합보드에 부가하여, 목제품 생산 후 발생하는 부산물인 편백나무 톱밥의 효율적인 이용과 건축내장재로의 응용을 목표로 목재섬유와 편백톱밥 및 녹차를 혼합한 복합보드를 제조하여 동적탄성률에 미치는 톱밥 및 녹차 배합비율의 영향 및 동적탄성률로부터 정적 휨강도성능의 예측가능성을 평가하였다. 목재섬유-톱밥-녹차 복합보드의 동적탄성률은 1.41~1.65 GPa의 범위에 있었고, 목재섬유: 톱밥: 녹차의 배합비율 50 : 40 : 10에서 가장 높은 값을 나타내었다. 이 값은 정적 휨 탄성계수의 1.4~1.6배의 높은 값을 나타내었고, 녹차-목재섬유복합보드보다 2.0~2.9배 낮은 값을 나타내었다. 동적탄성률과 정적 휨 강도성능과의 상관회귀에서는 일부 예외를 제외하고 대부분 매우 높은 상관계수가 확인되어, 양단자유 휨 진동에 의한 동적탄성률로부터 정적 휨강도성능의 예측이 비파괴적으로 가능할 것으로 사료된다. In this study, in addition to the green tea - wood fiber hybrid composite boards of previous researches, to make effective use of saw dust of domestic cypress tree with functionalities and application as interior materials, eco-friendly hybrid composite boards were manufactured from wood fiber, green tea and saw dust of cypress tree. We investigated the effect of the component ratio of saw dust and green tea on dynamic MOE (modulus of elasticity). Dynamic MOE was within 1.41~1.65 GPa, and showed the highest value in wood fiber : green tea : saw dust = 50 : 40 : 10 of the component ratio, and had the lowest value in 50 : 30 : 20 of component ratio. These values were 1.4~1.6 times higher than static bending MOE of wood fiber - saw dust - green tea hybrid composite boards, and were 2.0~2.9 times lower than those of green tea - wood fiber hybrid composite boards reported in the previous researches. From the results of correlation regression analyses between dynamic MOE and static strength performances, a very high correlation coefficients were obtained, therefore it was found that static bending strength performances can be estimated with a high reliability from dynamic MOE.